Fullness light. - Zhao, Cen. (2010)
The Chinese has a rich history of tradition and culture, which I have drawn many inspirations from in this project. I find this project began as an important journey for myself in understanding my own identity, as well as finding a point of reconciliation in today’s context in which I am referring to as modern and contemporary. I am looking to project this notion as a product encompassing the values and meaning that it could share with people from the same background or even crossing cultural boundaries, and in the meantime reinforcing a stronger sense of identity that is contemporarily Chinese.